Isolation and morphological characterisation of bovine adipose tissue derived stem cells - Fhataheya, Buang; Mohamed Zulkali, Mohamed Daud, Prof. Madya Dr.; Ku Syahidah, Ku Ismail; Ruszymah, Hj Idrus; Mukhzeer, Mohamad Shahimin, Dr. (Universiti Malaysia Perlis (UniMAP), 2012)
International Postgraduate Conference On Engineering (IPCE 2010), 16th - 17th October 2010 organized by Centre for Graduate Studies, Universiti Malaysia Perlis (UniMAP) at School of Mechatronic Engineering, Pauh Putra Campus, Perlis, Malaysia.